SPT-EFFECTIVE SHEAR PARAMETER CORRELATION FOR SOFT CLAY IN JAKARTA USING BIG DATA - Iskandar, Ali; Sentosa, Gregorius Sandjaja; Kawanda, Aksan; Yohana, Felicia; Tantobudiono, Felicia Refalina (JMTS: Jurnal Mitra Teknik Sipil, 2025)
This study aims to develop a practical model to estimate the shear strength parameters of clay soils, such as effective cohesion (c¢), angle of internal friction (f¢), and elasticity modulus in a more efficient and economical, by using Standard Penetration Test (SPT) and index properties data (including grain size analysis and Atterberg test). This study focuses on fine-grained soils (especially in Jakarta) in two consistency groups, namely very soft clay (C01, SPT 0-2 blows/ft) and soft clay (C02, SPT 2-4 blows/ft). The analysis was conducted by establishing a linear relationship between mean effective stress (p¢) and deviatoric stress (q), with an additional ±10% envelope to account for data variability. The results show that the linear regression of p¢-q adequately represents soil behavior for both consistency groups. The ±10% envelope successfully accommodates variations including the effect of plasticity index (PI), indicating that this model can serve as a practical alternative in geotechnical design when triaxial test data and undistrurbed sampling test are not available.